SISTEM INFORMASI AKADEMIK BERBASIS WEB MENGGUNAKAN PENDEKATAN BERORIENTASI OBJEK PADA JURUSAN TEKNOLOGI INFORMASI POLITEKNIK NEGERI PADANG - Ronal Hadi; Yulherniwati yulherniwati; Rika Idmayanti (Elektron : Jurnal Ilmiah, 2012)
Department of Information Technology Padang State Polytechnic growing rapidly, the number of students and the amount of data will increase too. However, these conditions will bring complex problems to the department to manage it in quantitative and qualitative way. How complicated the problems faced when there are a lot of data that needs to be processed, and if it goes wrong it needs a long time to find, fix and change it. To minimize the errors and redundancies in processing the data, the department requires an academic information system. This system will manage student grades, final assignment and job training data at Information Technology Department. This web based Academic Information System was develop by using object oriented concept and JAVA especially J2EE technology as programming language and MYSQL Server as database. This system also design by using UML(Unified Modeling Language).